Longitudinal effects of swimming on bone in adolescents: a pQCT and DXA study - Alejandro Gomez-Bruton; Alejandro Gonzalez-Aguero; Angel Matute- Llorente; Alba Gomez-Cabello; Jose A. Casajus; German Vicente-Rodríguez (Termedia Publishing House, 2017)
The aims of the present study were, firstly, to evaluate areal bone mineral density (aBMD), bone strength and structure during a swimming season and compare them to those of normo-active controls (CG), and secondly to ascertain whether practising an additional weight-bearing sport other than swimming might improve bone. Twenty-three swimmers who only swam (SWI-PURE; 14 males, 9 females), 11 swimmers who combined swimming with an additional weight-bearing sport (SWI-SPORT; 8 males, 3 females) and 28 controls (CG; 16 males, 12 females) participated in the present study. aBMD was assessed with dual energy X-ray (DXA). Bone mass, area, structure and strength of the non-dominant tibia and radius were measured with peripheral quantitative computed tomography (pQCT). Measurements were performed at the beginning of the swimming season and 8 months later. The only difference among groups for DXA and pQCT variables was found for arm aBMD, which was higher in the SWI-SPORT than in the CG group at both pre- and post-evaluation. Group by time interactions (GxT) were found for trochanter aBMD when comparing SWI-SPORT to CG and SWI-SPORT to SWI-PURE, favouring in both cases SWI-SPORT. No GxT were found for the radius. For the tibia, GxT were found between SWI-SPORT and CG and between SWI-PURE and CG, in both cases favouring the swimmers. A season of swimming does not confer any additional benefits to aBMD, but may confer minor benefits to structure and mass. Complementing swimming with a weight-bearing activity is beneficial to bone.